Protective role of Cecropin AD against LPS-induced intestinal mucosal injury in chickens - Zhi, Yan; Li, Tingyu; Li, Yaxuan; Zhang, Tao; Du, Mengze; Zhang, Qian; Wang, Xiangdong; Hu, Ge (Frontiers in Immunology, 2023)
Cecropin AD (CAD), a renowned antimicrobial peptide, has displayed promising therapeutic potential against various bacterial infections. This study aimed to investigate the protective effects of CAD against lipopolysaccharide (LPS)-induced intestinal adversities in chickens. Sixty SPF-grade chicks were divided into groups and exposed to different CAD dosages followed by LPS administration. Subsequent assays revealed that LPS significantly elevated the activity of Diamine oxidase (DAO), a marker for intestinal mucosal injury. However, treatment with CAD remarkably attenuated this increase, with high dosages demonstrating pronounced effects. Furthermore, CAD significantly mitigated LPS-induced oxidative stress in intestinal tissues, as evidenced by restored levels of antioxidants and reduced reactive oxygen species.Histological observations corroborated these findings, with CAD-treated groups exhibiting better-preserved villi structures. Additionally, CAD notably reduced the expression of inflammatory markers, including IL-6 and IL-8, post-LPS stimulation. Most pivotally, CAD effectively modulated the NLRP3 inflammasome pathway, curbing the expression of associated factors such as NLRP3, Caspase-1, This study revealed the therapeutic potential of Cecropin AD in ameliorating LPS-induced intestinal injuries, primarily via its anti-inflammatory and antioxidative mechanisms, and through the modulation of the NLRP3 inflammasome pathway.